(untitled) (Педагогіка вищої та середньої школи, 2003)
In article, the process of national self-consciousness forming is investigated as education science problem, are investigated central ways and means of forming this process in works of outstanding culture and education persons. It has been suggested that this problem should be analyzed in details on special courses at higher educational establishments with the purpose of developing personality-oriented education.